2021
DOI: 10.1186/s12884-021-03959-3
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the lederman Prenatal Self-Evaluation Questionnaire (PSEQ) in Brazil

Abstract: Background The Lederman Prenatal Self-Evaluation Questionnaire (PSEQ) is used to assess psychosocial adaptation to pregnancy, labor, childbirth, and maternity. The PSEQ is a tool used in various countries and has been translated into Portuguese; however, it needs to be validated in Brazil. This study aimed to analyze the validity and reliability of the PSEQ in Brazilian pregnant women. Method This methodological validity study investigated internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…In this study, item analysis methods, namely, correlation coefficient analysis and the critical ratio (CR) method, were used to screen the questionnaire items. The Pearson correlation coefficient method of total item scores was used to test and exclude entries with correlation coefficients < 0.40 [ 25 ]. The CR method was used to test whether the questionnaire items could identify the degree of reflection of different respondents, excluding items with a CR < 3.00 or not reaching a significant level ( p < 0.05) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, item analysis methods, namely, correlation coefficient analysis and the critical ratio (CR) method, were used to screen the questionnaire items. The Pearson correlation coefficient method of total item scores was used to test and exclude entries with correlation coefficients < 0.40 [ 25 ]. The CR method was used to test whether the questionnaire items could identify the degree of reflection of different respondents, excluding items with a CR < 3.00 or not reaching a significant level ( p < 0.05) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was tested for construct validity and internal consistency using 30 participants who were not included in the main analyses. Construct validity was assessed with the Pearson Product Moment correlation by correlating the score of each question with the total score [35]. The questionnaire was deemed valid when the correlation coefficient (r-value) exceeded the critical value [28].…”
Section: Usability Measurementmentioning
confidence: 99%
“…Then, the questionnaire was piloted in two rounds, each on 30 pharmacists from several provinces of Indonesia (1st round: 76.67% from West Java and 6.67% from Central Java; 2nd round: 26.67% from Central Java, 13.33% from South Sumatera, and 10% from West Java) (22). The 2nd round showed that the questionnaire was valid (all items have Pearson r > 0.361 in the construct validity test) and reliable (Cronbach's α of KAP sections >0.600) (23)(24)(25). Therefore, the final questionnaire consisted of six sections: eight questions on sociodemographic data, six on knowledge, 10 on attitudes, eight on practice, two open-ended questions about barriers and facilitators, and nine additional information regarding practice.…”
Section: Study Instrumentmentioning
confidence: 99%